Debt, Leases, Taxes, and the Endogeneity of Corporate Tax Status - Graham, John R.; Lemmon, Michael L.; Schallheim, James S. (Journal of Finance, 1998)
We provide evidence that corporate tax status is endogenous to financing decisions, which induces a spurious relation between measures of financial policy and many commonly used tax proxies. Using a forward-looking estimate of before-financing corporate marginal tax rates, we document a negative relation between operating leases and tax rates, and a positive relation between debt levels and tax rates. This is the first unambiguous evidence supporting the hypothesis that low tax rate firms lease more, and have lower debt levels, than high tax rate firms.